2017
DOI: 10.1111/php.12684
|View full text |Cite|
|
Sign up to set email alerts
|

An Ethenoadenine FAD Analog Accelerates UV Dimer Repair by DNA Photolyase

Abstract: Reduced anionic flavin adenine dinucleotide (FADH ) is the critical cofactor in DNA photolyase (PL) for the repair of cyclobutane pyrimidine dimers (CPD) in UV-damaged DNA. The initial step involves photoinduced electron transfer from *FADH to the CPD. The adenine (Ade) moiety is nearly stacked with the flavin ring, an unusual conformation compared to other FAD-dependent proteins. The role of this proximity has not been unequivocally elucidated. Some studies suggest that Ade is a radical intermediate, but othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…30 However, the change in local environment that is produced by the DNA presence may influence, both geometrically and energetically, a potential ET step from the flavin to the adenine. Furthermore, recent experiments, using photolyases with adenine-modified FAD, 31 support the possible occurrence of two-step hopping, but a radical anion intermediate of the modified adenine was not observed. Electronic structure calculations by Weber et al found that the protein environment surrounding the FADH anion favors strong electronic overlap between the flavin radical and the adenine moiety 32 (and therefore a large electronic coupling between them 33 ).…”
Section: ■ Introductionmentioning
confidence: 87%
“…30 However, the change in local environment that is produced by the DNA presence may influence, both geometrically and energetically, a potential ET step from the flavin to the adenine. Furthermore, recent experiments, using photolyases with adenine-modified FAD, 31 support the possible occurrence of two-step hopping, but a radical anion intermediate of the modified adenine was not observed. Electronic structure calculations by Weber et al found that the protein environment surrounding the FADH anion favors strong electronic overlap between the flavin radical and the adenine moiety 32 (and therefore a large electronic coupling between them 33 ).…”
Section: ■ Introductionmentioning
confidence: 87%
“…S10 †), which were selected as effective co-initiators based on our prior reports. 14,25 A Rehm-Weller analysis 34 was performed to identify the most likely mechanism for photoredox catalysis with the present 3-component system. Excited-state oxidation (E * ox ) and reduction (E * red ) potentials for the thiophene-fused BODIPYs were estimated using the singlet excited state energy, E S1 , calculated from the crossover in absorption and uorescence (emission) proles, in combination with ground state redox potentials obtained from cyclic voltammetry (Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the past 20 years, we have been focused on the light-driven function of photoflavoproteins (Gindt et al, 2016;Kodali, Siddiqui, & Stanley, 2009;Lee, Kodali, Stanley, & Matsika, 2016;MacFarlane IV & Stanley, 2001Narayanan, Singh, Kodali, Moravcevic, & Stanley, 2017;Pauszek, Kodali, Siddiqui, & Stanley, 2011Stanley & MacFarlane IV, 2000), and flavin dyads Yu et al, 2012). In either case, it is not the ground state electronic structure that is of interest but, rather, the excited electronic states.…”
Section: Motivationmentioning
confidence: 99%